Towards an asymmetric organocatalytic α-cyanation of β-ketoesters - Chowdhury, Raghunath (Tetrahedron Lett, 2015)
This communication describes the first proof of concept for an asymmetric α-cyanation of β-ketoesters using a hypervalent iodine-based electrophilic cyanide-transfer reagent. A series of different organocatalysts has been investigated and it was found that the use of naturally occurring Cinchona alkaloids allows obtaining the target products in good yields and with moderate enantioselectivities up to er = 76:24 under operationally simple conditions.